Getting Started: A Case for Intervention Research by School Social Workers - Christina L Helfrick; Tonya L Eberhart (International Journal of School Social Work, 2025)
School social workers are to be leaders in interdisciplinary collaboration, developing programs and interventions that are evidence-based and data driven. The need for intervention in school settings combined with social work values, provides a prime opportunity to lead through intervention development. The intervention development process is a six-phase process including: problem analysis and project planning, information gathering and synthesis, design, early development and pilot testing, evaluation and advanced development, and dissemination. This process is used to describe the development of the Champions for Teens, a homeless student advocate program, as an encouragement for other school social workers to do design, implement, and disseminate intervention research.
Keywords: School Social Work; homeless youth; intervention research; advocate; practice informed research